The Assessment of Creative Waterfronts: A Case Study of the Kyrenia Waterfront - Uzumcuoglu, Doga; Polay, Mukaddes (Mdpi, 2022)
Nowadays, cities exhibit a high degree of culture, innovation, knowledge, and advanced technology. Therefore, talented people or the creative class have become the focal point of contemporary cities. The productivity of cities affects the economy, attractiveness, and awareness level of society. Economic, socio-cultural, and demographic changes in Kyrenia Waterfront have altered visitors' expectations; they expect to experience adequate physical quality, practical opportunities, and a collaborative atmosphere. By surveying 247 randomly selected users and conducting site observations, this study aimed to assess user satisfaction at Kyrenia Waterfront and clarify its impacts on the immediate local context. Statistical analysis of the resulting data allowed us to determine the socio-demographic characteristics of respondents, creative environmental aspects, waterfront development aspects, and creative waterfront aspects of the Kyrenia Waterfront through the use of SPSS and AMOS. This study revealed that most respondents perceive the waterfront as a positive contribution to the area. On the other hand, the results affirmed that physical quality, practical opportunities, and integration of innovation and technology need to be improved. The process suggests that the viewpoints of locals, visitors, and creative people should be considered in planning and design decisions to contribute to the sufficiency of creative waterfronts.
Keywords: waterfronts; urban development; factor analysis; creative environment; Kyrenia Waterfront